Enhancing Methodologies for Developing Students' Communicative Competencies in English (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The development of students' communicative competencies in English has emerged as a key priority in higher education worldwide. This article explores innovative methodologies and practices designed to enhance English language teaching, with a focus on communicative skills. Drawing from contemporary research and practical applications, the article provides insights into theoretical foundations, pedagogical models, and strategies that contribute to effective teaching. The discussion is rooted in the context of Uzbekistan's educational reforms, emphasizing the importance of aligning teaching methods with global standards.